2012
DOI: 10.1007/s10393-012-0763-9
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropy of Wild Mammals as a Determinant of Emerging Infectious Diseases in the Asian–Australasian Region

Abstract: Humans create ecologically simplified landscapes that favour some wildlife species, but not others.Here, we explore the possibility that those species that tolerate or do well in human-modified environments, or 'synanthropic' species, are predominantly the hosts of zoonotic emerging and re-emerging infectious diseases (EIDs). We do this using global wildlife conservation data and wildlife host information extracted from systematically reviewed emerging infectious disease literature. The evidence for this relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 69 publications
4
93
2
3
Order By: Relevance
“…Other species showed more generalist tendencies such as R. tanezumi, which was found in all types of habitat analyzed, including households. McFarlane et al (2012) used the terms "synanthropic species, " to refer to species ecologically associated with humans, and "generalist" species, to mean ubiquitous species that are able to live in peridomestic environments and/or are able to invade disturbed habitats. McFarlane et al (2012) showed that the rodent species known to be reservoirs of zoonotic emerging infectious diseases are most likely found in human-modified environments.…”
Section: Dependent Independentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species showed more generalist tendencies such as R. tanezumi, which was found in all types of habitat analyzed, including households. McFarlane et al (2012) used the terms "synanthropic species, " to refer to species ecologically associated with humans, and "generalist" species, to mean ubiquitous species that are able to live in peridomestic environments and/or are able to invade disturbed habitats. McFarlane et al (2012) showed that the rodent species known to be reservoirs of zoonotic emerging infectious diseases are most likely found in human-modified environments.…”
Section: Dependent Independentmentioning
confidence: 99%
“…McFarlane et al (2012) used the terms "synanthropic species, " to refer to species ecologically associated with humans, and "generalist" species, to mean ubiquitous species that are able to live in peridomestic environments and/or are able to invade disturbed habitats. McFarlane et al (2012) showed that the rodent species known to be reservoirs of zoonotic emerging infectious diseases are most likely found in human-modified environments. In this study, the synanthropic species R. exulans showed high specialization to settlement habitat, whilst the other synanthropic species R. tanezumi showed low specialization.…”
Section: Dependent Independentmentioning
confidence: 99%
“…Recently, two concepts have emerged: (1) 'synanthropic species', namely species ecologically associated with humans; and (2) 'generalist' species, which are species living in peridomestic habitats or those that often invade disturbed habitats (McFarlane et al 2012). In a comparative study performed in the Asian-Australian region, McFarlane et al (2012) found that wild mammal hosts (primarily rodents and bats) of zoonotic emerging infectious diseases are 15-fold more likely to inhabit human-modified environments.…”
Section: Identifying Rodent Habitat Preferencesmentioning
confidence: 99%
“…In a comparative study performed in the Asian-Australian region, McFarlane et al (2012) found that wild mammal hosts (primarily rodents and bats) of zoonotic emerging infectious diseases are 15-fold more likely to inhabit human-modified environments. That is, human-induced disturbances often increase the distribution and abundance of generalist rodent species, which are frequently important reservoirs of human pathogens.…”
Section: Identifying Rodent Habitat Preferencesmentioning
confidence: 99%
“…To examine the hypothesis that ecological change accounts for a substantial component of the rise in zoonotic EIDs, a series of transdisciplinary studies based on the Australasian region were designed by the author under the doctoral supervision of Professors Tony McMichael and Adrian Sleigh and Dr Peter Black (McFarlane et al, , 2012(McFarlane et al, , 2013(McFarlane et al, , 2014. These studies reflected Tony's support for research that explored the awkward, important issues, and for epidemiology that -in an inventive and insightful way -sought to address these challenges.…”
Section: Patterns Of Eids In the Australasian Regionmentioning
confidence: 99%